Cytotoxicity and genotoxicity of cucurbitacin-containing phytonematicides and related bioavailability in tomato plant - Mashela, Tshepo Segwadi (My University, 2025)
The withdrawal of synthetic chemical nematicides from the agrochemical market has left farmers with limited options to manage plant parasitic nematodes. Currently, the indigenous plants Curcumis myriocupus and Cucurmis africunus fruits are utilized to develop Nemarioc-AL and Nemafric-BL phytonematicides at the University of Limpopo, South Africa. These noble products are effective on nematode suppression on different crops. The products are environmentally friendly and cost effective compared to synthetic chemical nematicides which cost a fortune. The two products are viewed as a future bionematicide. However, more information is required on safety to non-target organisms which can be negatively affected by the product during application. Although bionematicides are viewed as a potential product, to manage nematodes, less than 1% are currently registered in the agrochemical market. Registration authorities have not formulated the legislative framework for botanicals as alternative agricultural remedies to the withdrawn synthetic chemicals. This study consists of five objectives (i) investigate the bioavailability of Nemarioc-AL and Nemafric-BL phytonematicides in plant tissues and chemical residues in different soil types. (ii) examine whether exposure of earthworms to Nemafric-BL or Nemarioc-AL phytonematicides would affect earthworm protein content. (iii) determine whether exposure of Raw 264.7 macrophage cells to Nemarioc-AL and Nemafric-BL phytonematicides would have cytotoxic effects. (iv) investigate whether short-term dermal and oral exposure to Nemarioc-AL and Nemafric-BL phytonematicides would induce mortality or any structural deformities on earthworms. To achieve these objectives, reliability of measured variables was ensured by using statistical levels of significance (P ≤ 0.05) and coefficient of determination (R2), with validity ensured by conducting three independent experiments over time. The bioavailability of cucurbitan A and B was observed in tomato fruits, leaves, stems, roots and soil treated by Nemarioc-AL and Nemafric-BL phytonematicides. At 150 days after application of Nemarioc-AL phytonematicide, the accumulation of cucurbitacin A in tomato fruits was not detected, while cucurbitacin B was detected. Sandy loam (+), had the highest concentration of cucurbitacin B(0.034 mg/kg), followed by red soil with 0.027 mg/kg, then sandy soil with 0.022 mg/kg and red soil with 0.20 mg/kg. No bioavailability of both cucurbitacin’s was detected in the untreated controls. In contrast, the highest cucurbitacin B accumulation was detected in red soil, followed by dark soil, then followed sandy soil and sandy loam (+) with an average mean of 0.034, 0.028, 0.025 and 0.026, respectively. Using the biological indices generated from Curve-fitting Allelochemical Response Dose (CARD) computer- algorithm model a MCSP of Nemarioc-AL phytonematicide on tomato plants inoculated by earthworms was successfully developed at 1.09%, with the overall sensitivity (Σk) value of 1 unit. Nemafric-BL phytonematicide had a computed MCSP of 1.35%, with the overall sensitivity (Σk) value of 2 unit. Proteomics, using one dimensional electrophoresis gel, lower concentrations of Nemarioc-AL phytonematicide 2 and 4% has shown shallow bands, while high concentrations (4, 8, 16, 32 and 64%) showed intensified bands of proteins. The MTT assay was used to assess toxicity of Nemarioc-AL and Nemafric-BL phytonematicides on murine Raw 264.7 macrophages. The increasing concentration of Nemarioc-AL phytonematicide exhibited 50% cytotoxic effects to cell viability of Raw 264,7 cell line at 5 and 10 mg/mL relative to untreated and curcumin treated control. Similarly, Nemafric-BL phytonematicides, showed 50% cytotoxicity at 5 and 10 mg/mL. As the concentrations of Nemarioc-AL and Nemafric-BL phytonematicides decreased from 1.25 to 0.078 mg/mL, the cell viability of Raw 264.7 cell lines were stimulated relative to positive control. Lower concentrations of phytonematicides showed moderate to no cytotoxicity on Raw 264.7 cell lines. While higher concentrations have shown higher degree of cytotoxicity. Lower concentrations (2-8%) of both phytonematicides did not impact the earthworm's viability, while at 16 to 64%, they were no viability observed. Less structural deformities were observed at 2 to 8% concentration, while at higher concentrations have shown more structural deformities indicating sings of toxicity. The major findings for this study were Nemarioc-AL and Nemafric-BL phytonematicides have shown less toxicity at lower concentrations levels, suggesting that it wont affect non-target species. These findings will help the University of Limpopo to further register these products in the agrochemical market
Thesis (Ph.D. Agriculture (Plant Production)) -- University of Limpopo, 2025
Keywords: Nematicides; Curcumis myriocupus; Bioavalability; Plant nematodes; Nematocides; Tomatoes